2017
DOI: 10.1017/s1049023x17006410
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Injury in Lagos, Nigeria: Assessing Prehospital Care

Abstract: Less than three percent among the victims of road crashes had formal prehospital care and shorter hospital arrival time. Current facilities for emergency prehospital care in Lagos are inadequate and require improvement. Training lay first-responders, who bring the majority of the injured to hospital, in basic first-aid may improve prehospital care in Lagos. Ibrahim NA , Ajani AWO , Mustafa IA , Balogun RA , Oludara MA , Idowu OE , Solagberu BA . Road traffic injury in Lagos, Nigeria: assessing prehospital care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
1
33
1
3
Order By: Relevance
“…The motorcycle was a common mode of travel for women, especially in remote areas as well as areas prone to significant traffic. However, it is important to bear in mind that beyond the risk posed by these two-wheelers to pregnant women, at least 30% of road traffic accidents have been attributed to them [40]. It was, therefore, good to find that women in our study perceived the tricycle as a safer alternative.…”
Section: Discussionmentioning
confidence: 75%
“…The motorcycle was a common mode of travel for women, especially in remote areas as well as areas prone to significant traffic. However, it is important to bear in mind that beyond the risk posed by these two-wheelers to pregnant women, at least 30% of road traffic accidents have been attributed to them [40]. It was, therefore, good to find that women in our study perceived the tricycle as a safer alternative.…”
Section: Discussionmentioning
confidence: 75%
“…Most of the victims were young males in their most productive prime of life, the economic life-wires of most homes in sub-Saharan Africa. Most are from the low-income economic strata of the population, a group well-documented to bear the greatest proportion of the global RTI burden ( 8 , 10 , 13 , 14 , 22 , 23 ). This fact has well-known significant debilitating implications for a nation’s human capital base.…”
Section: Discussionmentioning
confidence: 99%
“…Although a global phenomenon, RTI burdens in general, and RTI-related fatalities in particular, exert their highest tolls in the low middle-income countries (LMIC) of the world ( 1 , 5 7 ). It is particularly more so in the African region ( 1 , 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the second finding, our study showed that LASAMBUS attended to less than half of the RTA calls that it received. Similarly, a 2017 single-institution study revealed that, of all the RTAs that came into the emergency department of a tertiary health facility, the Lagos State University Teaching Hospital (LASUTH), less than 3% were brought in by LASAMBUS [22].…”
Section: Discussionmentioning
confidence: 99%